Product Quality Control Using QCC, FMECA and RCA Methods at PT Tirta Sukses Perkasa - Wardatul Maulia; Wiwik Sulistiyowati (Universitas Muhammadiyah Sidoarjo, 2022)
Quality control is one of the keys to the success of a company. PT Tirta Sukses Perkasa is a manufacturer of Bottled Drinking Water (AMDK) that strives to improve the quality of its goods in order to satisfy customers. The goal is to be able to identify the elements that can affect product failure or defects in order to produce results that meet consumer expectations. This study can find the main problem that results in excessive product defects by using the Quality Control Circle (QCC) approach. The next stage of analysis uses the Failure Mode Effect and Criticality Analysis (FMECA) approach to examine the problem thoroughly by setting the highest Risk Priority Number (RPN) to then be analyzed using Root Cause Analysis (RCA) to find the root cause of the problem that can lead to defective products. The results of the QCC analysis of five types of product defects in the 600 ml bottle were found to be the dominant factor in the bottom silver defect with a total of 378 defective products. The results of the FMECA analysis have the highest RPN value on bottom silver with a value of 432> 324, which means it is very critical and the risks incurred are unacceptable. The results of the RCA analysis on product defects that have the highest RPN value include several factors, including human factors, machines, and raw materials. Recommendations for improvement are in the form of SOPs for setting machines and sorting raw materials before the production process and always monitoring production operators.